PURCHASE DECISION: THE ROLE OF STORE ATMOSPHERE AND PRODUCT QUALITY - Pebi Kurniawan; Ali Jufri; Santika Gumilang; Tedi Kustandi (Dinasti International Journal of Management Science, 2022)
The latest trend of the coffee cafe business is one of the businesses that is in great demand by business actors in Indonesia. The number of coffee cafes creates perfect competition with the trend of creating a cafe atmosphere that has an interior design and development of a natural atmosphere or a certain nuance. The purpose of the study was to determine the role of store atmosphere and product quality on purchasing decisions at the Kompanyon café. This study uses quantitative research methods with questionnaire research instruments. The results of the study partially store atmosphere affect purchasing decisions and the quality of the product affects the purchasing decision. Simultaneous test results store atmosphere and product quality affect purchasing decisions. These results become material for further studies regarding more dynamic determinants in decision making.